The Effectiveness of Peaceful Education Learning Strategies for Students at Emergency Madrasas Following Natural Disasters in Sidoarjo - Abd Rachman Assegaf; Hani Khaulasari; Muhammad Thohir; Amjad Ali; Ratna Pangastuti (Jurnal Pendidikan Agama Islam, 2025)
Purpose – This research aims to develop and evaluate learning strategies and curricula focused on risk management education for emergency schools in post-disaster areas. The goal is to support a peaceful learning process that helps students recover from trauma while improving motivation, academic performance, and disaster preparedness.